Record of ascending passage of potamotrygonid stingrays through navigation locks: Implications for the management of non-native species in the Upper Paraná River basin, Southeastern Brazil - Garrone-Neto, Domingos [UNESP]; Haddad, Vidal [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP] (Regional Euro-Asian Biological Invasions Centre Oy (REABIC), 2014)
In this paper we tested the hypothesis that potamotrygonid stingrays are expanding their distribution to novel areas via artificial passages constructed for river navigation in the Upper Paraná River basin, Southeastern Brazil. Individuals of Potamotrygon falkneri and Potamotrygon motoro were captured, fitted externally with t-bar anchor tags, and released downstream of the Jupiá Dam – a hydro power plant constructed in the 1970s that has no fish pass system, but had a navigation lock installed in 1998 for the movement of ships. A total of 182 stingrays were marked, and recaptures of individuals of both species occurred within a period of two to 12 months after the first capture, with recapture rates around 5% for P. falkneri (n=6) and 3% for P. motoro (n=2). Two individuals of P. falkneri were recaptured upstream of the Jupiá Dam, about eight kilometers from the first capture site. This fact attests to the ability of stingrays to overcome artificial barriers such as hydro power plants through navigation locks. The Upper Paraná River basin is densely populated, so the spread of potamotrygonids will increase the risk of injury from stingrays’ barbs. Their use of navigation locks is relevant for management actions, including reducing the risk of human-stingray interactions.
Keywords: Alien species; Biological invasions; Environmental impact; Mark and recapture method; Potamotrygonidae; Spatial ecology